Factors associated with depression in the patients with diabetes mellitus type 2 - Šabanović, Admir; Maksimović, Nataša; Stojanović-Tasić, Mirjana; Bakić, Marijan; Grgurević, Anita D (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The assessment of association of depression and diabetes mellitus type 2 using the Patient Health Questionaire (PHQ-9) has not been done in Montenegro. The aim of this study was to assess the prevalence of depression in the patients with type 2 diabetes mellitus, and to identify the risk factors associated with the presence of depression. Methods. A cross-sectional study was conducted at the General Hospital in Bijelo Polje, from July to September, 2015. It included 70 patients over 35 years of age with the diagnosis of diabetes for at least six months. For the assessment of depression presence and intensity PHQ–9 was used. All variables associated with the presence of depression at a significance level of p < 0.05 were included into the final method of the multivariate logistic regression analysis. Results. Comorbidities were statistically significant more frequent among patients with depression (χ2 = 5.40; p = 0.020). Duration of diabetes over five years was significantly associated with depression (χ2 = 12.48; p < 0.001). Depression occurred more frequently among physically inactive subjects (χ2 = 10.74; p = 0.005). The presence of diabetic polyneuropathy (χ2 = 6.04; p = 0.014) and cataract (χ2 = 5.351; p = 0.021) were also significantly associated with depression. A multivariate logistic regression analysis showed that the duration of diabetes over five years and presence of cataract were independently associated with depression. Conclusion. The risk factors for depression among the subjects with diabetes were disease duration more than five years and the presence of cataract. Since depression is a serious disease and can be a risk factor for many chronic diseases, the best way of prevention is its early detection and treatment.
Keywords: depression; diabetes mellitus, type 2; patient health questionnaire; montenegro